Porphyry to epithermal transition in the altar Cu-(Au-Mo) deposit, Argentina, studied by cathodoluminescence, LA-ICP-MS, and fluid inclusion analysis - Maydagán, Laura (2014)
The middle to late Miocene Altar porphyry Cu-(Au-Mo) deposit, located in the Andean Main Cordillera of San Juan Province (Argentina), is characterized by the superposition of multiple vein generations consisting of both porphyry-type and high sulfidation epithermal-style alteration and mineralization. We constrain the physical and chemical evolution of the hydrothermal fluids that formed this deposit based on description and distribution of vein types, scanning electron microscopy, cathodoluminescence (CL) imaging, trace elements in quartz veins, and fluid inclusion microthermometry. Quartz CL textures and trace elements (chiefly Li, Al, Ti, and Ge) differentiate among quartz generations precipitated during different mineralization and alteration events. Early quartz ± chalcopyrite ± pyrite veins and quartz ± molybdenite veins (A and B veins) show considerable complexity and were commonly reopened, and some underwent quartz dissolution. Early quartz ± chalcopyrite ± pyrite veins (A veins) are dominated by equigranular bright CL quartz with homogeneous texture. Most of these veins contain higher Ti concentrations than any other vein type (average: 100 ppm) and have low to intermediate Al concentrations (65-448 ppm). Quartz ± molybdenite (B veins) and chlorite + rutile ± hematite (C veins) veins contain quartz of intermediate CL intensity that commonly shows growth zones with oscillatory CL intensity. Quartz from these veins has intermediate Ti concentrations (∼20 ppm) and Al concentrations similar to those of A veins. Quartz from later quartz + pyrite veins with quartz + muscovite ± tourmaline halos (D veins) has significantly lower CL intensity, low Ti (<15 ppm) and elevated Al concentrations (up to 1,000 ppm), and typically contains euhedral growth zones. Late veins rich in sulfides and sulfosalts show CL textures typical of epithermal deposits (dark CL quartz, crustiform banding, and euhedral growth zones). Quartz from these veins typically contains less than 5 ppm Ti, and Al, Li, and Ge concentrations are elevated relative to other vein types. Based on experimentally established relationships between Ti concentration in quartz and temperature, the decrease in Ti content in successively later quartz generations indicates that the temperature of the hydrothermal fluids decreased through time during the evolution of the system. Vein formation at Altar occurred at progressively lower pressure, shallower paleodepth, and lower temperature. Under lithostatic pressures, the magma supplied low-salinity aqueous fluids at depths of ∼6 to 6.8 km (pressures of 1.6-1.8 kbar) and temperatures of 670° to 730°C (first quartz generation of early quartz ± chalcopyrite ± pyrite veins). This parental fluid episodically depressurized and cooled at temperatures and pressures below the brine-vapor solvus. Quartz ± molybdenite veins precipitated from fluids at temperatures of 510° to 540°C and pressures of 800 to 1,000 bars, corresponding to depths of 3 to 3.7 km under lithostatic pressures. Further cooling of hydrothermal fluids to temperatures between 425° and 370°C under hydrostatic pressures of 200 to 350 bars produced pyrite-quartz veins and pervasive quartz + muscovite ± tourmaline and illite alteration that overprinted the early hydrothermal assemblages. Late veins rich in sulfides and sulfosalts that overlapped the deep and intermediate high-temperature veins formed from fluids at temperatures of 250° to 280°C and pressures of 20 to 150 bars. The epithermal siliceous ledges formed from low-temperature fluids (<230°C) at hydrostatic pressures of <100 bars corresponding to depths of <<1 km.